맞춤형방문건강관리사업의 지역사회 네트워크 탐색 - 장숙랑(Soong-Nang Jang); 조성일(Sung-Il Cho) (保健敎育健康增進學會誌, 2012)
Objectives: The nurse visiting health service named Customized Visiting Health Care Program(CVHCP) requires the service innovations incorporating community support into a local service network. The purpose of this study was to assess the community network in CVHCP and inform improvement in this network. Methods: We used Social Network Analysis(SNA) in one CVHCP at H city. Network links were generated by self-administered questionnaires by the 14 community resource centers who quantified their links to all other 25 agents on the list. Links were analyzed by a dichotomous scale for any experience of collaboration and a scored scale of 0 to 3 for level of collaboration using UCINET v6. Results: A list of 14 agents was generated, and local network was dominated by the Public Health Center and a local welfare center named Unlimited Care Center(UCC). According to centrality score, UCC was the most prominent agent, and Public Health Center was the most influential agent, being a link in the pathway flow between other agents for 9.5% of contribution. CVHCP scored lower rank of prominent with 30.8% of other agents reported referring to it. Conclusions: Social network analysis provides a useful network description for informing and evaluation service network improvement in maximizing its service for the CVHCP.